Cognitive aids in strategy - Sund, Kristian J.; Galavan, Robert J.; Gustafsson, Robin (New horizons in managerial and organizational cognition., 2023)
Strategy research and practice has a long tradition of using frameworks, models, tools, and processes to describe, and guide the strategy work of managers. These are the cognitive aids that guide cognition, i.e., the way managers make sense of the world. Why, and how, do these tools interact with cognition? The sixth volume in the New Horizons in Managerial and Organizational Cognition series examines cognitive aids in strategy. Cognitive aids of strategy have a profound impact on the way managers learn about, conceptualize, share, and enact strategy and strategies in their organizations, yet these aids are often presented without reference to the underlying cognitive theory that might explain why the aid is useful. Cognitive Aids in Strategy brings together contributions by twelve strategy scholars, reflecting on a range of cognitive aids and their theoretical foundations, focusing attention on the importance of cognitive aids in strategy, and inspiring further research. It represents a new horizon for the study of managerial and organizational cognition.